Successful Treatment of Community-Acquired Methicillin-Resistant Staphylococcus Aureus Necrotizing Pneumonia in the Setting of Chronic Graft-Versus-Host Disease - Renduchintala, Kavita (Cureus, 2021)
Necrotizing pneumonia (NP) is a rare complication of community-acquired pneumonia that results in tissue necrosis and permanent destruction of the lung parenchyma. This study presents a case of a 21-year old male patient with T-cell acute lymphoblastic lymphoma who was treated with chemotherapy and matched-unrelated donor stem cell transplantation. His post-transplant course included chronic graft-versus-host disease (GVHD) and subsequent community-acquired methicillin-resistant Staphylococcus aureus (CA-MRSA) necrotizing pneumonia. In addition to antibiotics, steroids were used to help blunt the proinflammatory response following CA-MRSA pneumonia and this led to a rapid improvement in our patient’s clinical course. CA-MRSA pneumonia is often treated with vancomycin. Given the nature of necrotizing pneumonia, the use of a toxin reducing agent like linezolid and adjunct therapy with corticosteroids was beneficial in the management of this disease process in our patient with chronic GVHD. Further prospective studies are needed to evaluate this regimen as a therapeutic alternative.